2009
DOI: 10.1007/s11064-009-0108-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ionized Calcium-binding Adapter Molecule 1-Immunoreactive Microglia in the Spinal Cord Between Young Adult and Aged Dogs

Abstract: Microglia are main form of active immune defense, and they are constantly moving and analyzing the CNS for damaged neurons and infectious agents. In this study, we compared microglia in the spinal cord of the young adult (1-2 years old) and aged (10-12 years old) German Shepherd dogs via immunohistochemistry and western blot analysis for ionized calcium-binding adapter molecule 1 (Iba-1), a microglial marker. In addition, we also observed the interferon-gamma (IFN-gamma), a pro-inflammatory cytokine, and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 35 publications
5
19
1
Order By: Relevance
“…Tillakaratne et al [12,39] reported an increase in GAD67 in the below level of hemisected spinal cord in the cat, and they suggested that increases of GAD67 and GABA synthesis might response to maintain the cells in a default state. We recently reported that, in the aged dog spinal cord, increases of activated microglia, inflammatory cytokines, IFN-c and interleukin-1ß were found without distinct neuronal loss [37]. In conclusion, with other and our results, increases in two isoforms of GAD in the aged lumbar spinal cord may be associated with aged condition in the aged spinal cord.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Tillakaratne et al [12,39] reported an increase in GAD67 in the below level of hemisected spinal cord in the cat, and they suggested that increases of GAD67 and GABA synthesis might response to maintain the cells in a default state. We recently reported that, in the aged dog spinal cord, increases of activated microglia, inflammatory cytokines, IFN-c and interleukin-1ß were found without distinct neuronal loss [37]. In conclusion, with other and our results, increases in two isoforms of GAD in the aged lumbar spinal cord may be associated with aged condition in the aged spinal cord.…”
Section: Discussionsupporting
confidence: 84%
“…It was reported that no significant neuronal loss was examined in the spinal cord of aged dogs [37].…”
Section: Discussionmentioning
confidence: 95%
“…Two different antibodies against Iba1 have been used. The first one was obtained from Wako and recognizes a single band of about 17 kDa on Western blot, as expected for Iba1 (Chung et al, 2010;Deren et al, 2010). The second one was the polyclonal ab5076 Iba1 antibody from ABCAM.…”
Section: Immunostainingmentioning
confidence: 99%
“…In both adult and aged groups, we found that the staining pattern and number of NeuN (a marker for neurons) immunoreactive neurons were similar in both groups [27][28][29].…”
Section: Neun Immunoreactivitymentioning
confidence: 72%
“…These animals, which have given three paper [27][28][29], did not show any clinical nor any other signs in neural disorders. The handling and the care of the animals conformed to the guidelines established in order to comply with current international laws and policies (NIH Guide for the Care and Use of Laboratory Animals, NIH Publication No.…”
Section: Experimental Animalsmentioning
confidence: 77%